Pilot phase experience of the International Quality Improvement Collaborative catheterization registry. Issue 1 (15th April 2020) - Barry, Oliver M.; Ali, Fatima; Ronderos, Miguel; Sudhaker, Abish; Kumar, R. Krishna; Mood, Marhisham C.; Corona‐Villalobos, Carlos; Nguyen, Dinh Toai; Doherty‐Schmeck, Kaitlin; Bergersen, Lisa; Gauvreau, Kimberlee; Jenkins, Kathy J.; et al.
Abstract: Objectives: To describe the development of a quality collaborative for congenital cardiac catheterization centers in low and middle‐income countries (LMICs) including pilot study data and a novel procedural efficacy measure. Background: Absence of congenital cardiac catheterization registries in LMICs led to the development of the International Quality Improvement Collaborative Congenital Heart Disease Catheterization Registry (IQIC‐CHDCR). As a foundation for this initiative, the IQIC is a collaboration of pediatric cardiac surgical programs from LMICs. Participation in IQIC has been associated with improved patient outcomes. Methods: A web‐based registry was designed through a collaborative process. A pilot study was conducted from October through December 2017 at seven existing IQIC sites. Demographic, hemodynamic, and adverse event data were obtained and a novel tool to assess procedural efficacy was applied to five specific procedures. Procedural efficacy was categorized using ideal, adequate, and inadequate. Results: A total of 429 cases were entered. Twenty‐five adverse events were reported. The five procedures for which procedural efficacy was measured represented 48% of cases ( n = 208) and 71% had complete data for analysis ( n = 146). Procedure efficacy was ideal most frequently in patent ductus arteriosus (95%) and atrial septal defect (90%) device closure, and inadequate most frequently in coarctation procedures (100%), and aortic and pulmonary valvuloplasties (50%). Conclusions: The IQIC‐CHDCR has designed a feasible collaborative to capture catheterization data in LMICs. The novel tool for procedural efficacy will provide valuable means to identify areas for quality improvement. This pilot study and lessons learned culminated in the full launch of the IQIC‐CHDCR.